Comorbidities of patients in tiotropium clinical trials: comparison with observational studies of patients with chronic obstructive pulmonary disease - Miravitlles M; Price D; Rabe KF; Schmidt H; Metzdorf N; Celli B (International Journal of COPD, 2015)
Marc Miravitlles,1 David Price,2 Klaus F Rabe,3,7 Hendrik Schmidt,4 Norbert Metzdorf,5 Bartolome Celli6 1Pneumology Department, Hospital Universitari Vall d’Hebron, Ciber de Enfermedades Respiratorias (CIBERES), Barcelona, Spain; 2Academic Primary Care, Division of Applied Health Sciences, University of Aberdeen, Aberdeen, UK; 3Department of Medicine, Christian-Albrechts-Universität zu Kiel (CAU), Großhansdorf, Germany; 4Global Biometrics and Clinical Applications, Boehringer Ingelheim Pharma GmbH and Co KG, Ingelheim am Rhein, Germany; 5TA Respiratory Diseases, Boehringer Ingelheim Pharma GmbH and Co KG, Ingelheim am Rhein, Germany; 6Pulmonary Division, Brigham and Women’s Hospital, Boston, MA, USA; 7LungenClinic Grosshansdorf, Großhansdorf, Germany Background: There is an ongoing debate on whether patients with chronic obstructive pulmonary disease (COPD) seen in real-life clinical settings are represented in randomized controlled trials (RCTs) of COPD. It is thought that the stringent inclusion and exclusion criteria of RCTs may prevent the participation of patients with specific characteristics or risk factors.Methods: We surveyed a database of patients recruited into 35 placebo-controlled tiotropium RCTs and also conducted a systematic literature review of large-scale observational studies conducted in patients with a documented diagnosis of COPD between 1990 and 2013. Patient demographics and comorbidities with a high prevalence in patients with COPD were compared between the two patient populations at baseline. Using the Medical Dictionary for Regulatory Activities (MedDRA; v 14.0), patient comorbidities in the pooled tiotropium RCTs were classified according to system organ class, pharmacovigilance (PV) endpoints, and Standardised MedDRA Queries to enable comparison with the observational studies.Results: We identified 24,555 patients in the pooled tiotropium RCTs and 61,361 patients among the 13 observational studies that met our search criteria. The Global initiative for chronic Obstructive Lung Disease (GOLD) staging of patients in the RCTs differed from that in observational studies: the proportion of patients with GOLD stages I+II disease ranged from 40.0% to 51.5% in the RCTs but 24.5% to 44.1% in the observational studies; for GOLD stage III or IV disease these ranges were 7.2%–45.8% (RCTs) and 13.7–42.1% (observational studies). The comorbidities with the highest prevalence reported in the RCTs and observational studies were: hypertension (39.4%–40.0% vs 40.1%–60.6%), other ischemic heart disease (12.3%–14.2% vs 12.5%–41.0%), diabetes (10.3%–10.9% vs 4.0%–38.9%), depression (8.5%–9.5% vs 17.0%–20.6%), and cardiac arrhythmia (7.8%–11.4% vs 11.3%–15.8%).Conclusion: The clinical profile of COPD patients treated in the tiotropium trial program appears to be largely in the range of clinical characteristics, including cardiovascular comorbidities, reported for “real-life patients.” The tiotropium RCTs tended to include patients with more severe disease than the observational studies. Keywords: patient population, baseline characteristics, epidemiology, real-life patients, GOLD staging